Connecting real world with virtual space - Choo, Wei Liang. (2012)
NTU Co-Space, an implementation of a virtual world replica of NTU with realistic 3D models of the entire campus, allows users to explore NTU through their own virtual avatar. Through this player avatar, users are able to travel to different parts of the campus, interact with intelligent NPCs as well as other players. Implemented as a web version that works on Windows and Mac OS, this ties NTU Co-Space to laptops and desktops which lack mobility and ease of usage. The iPad version of NTU Co-Space brings about a mobility and ease of usage that comes with a tablet. It gives a whole new dimension to the way users interact with NTU Co-Space.